Leaf traits variation during leaf expansion in Quercus ilex L. (Photosynthetica, 2009)
The morphological, anatomical and physiological variations of leaf traits were analysed during Quercus ilex L. leaf expansion. The leaf water content (LWC), leaf area relative growth rate (RGRl ) and leaf dry mass relative growth rate (RGRm) were the highest (76±2 %, 0.413 cm 2 cm –2 d –1 , 0.709 mg mg –1 d –1 , respectively) at the beginning of the leaf expansion process (7 days after bud break). Leaf expansion lasted 84±2 days when air temperature ranged from 13.3±0.8 to 27.6±0.9 °C. The net photosynthetic rate (PN), stomatal conductance (gs ), and chlorophyll content per fresh mass (Chl) increased during leaf expansion, having the highest values [12.62±1.64 µmol (CO2) m –2 s –1 , 0.090 mol (H2O) m –2 s –1 , and 1.03±0.08 mg g –1 ,respectively] 56 days after bud break. Chl was directly correlated with leaf dry mass (DM) and PN. The thickness of palisade parenchyma contributed to the total leaf thickness (263.1±1.5 μm) by 47 %, spongy layer thickness 38 %, adaxial epidermis and cuticle thickness 9 %, and abaxial epidermis and cuticle thickness 6 %. Variation in leaf size during leaf expansion might be attributed to a combination of cells density and length, and it is confirmed by the significant (p<0.001) correlations among these traits. Q. ilex leaves reached 90 % of their definitive structure before the most severe drought period (beginning of June – end of August). The high leaf mass area (LMA, 15.1±0.6 mg cm –2 ) at full leaf expansion was indicative of compact leaves (2028±100 cells mm –2 ). Air temperature increasing might shorten the favourable period for leaf expansion, thus changing the final amount of biomass per unit leaf area of Q. ilex.

Environmental induced variations in leaf dark respiration and net photosynthesis of Quercus ilex L. (Photosynthetica, 2007)
The relationships between dark respiration rate (RD) and net photosynthetic rate (PN) in Quercus ilex L. shrubs growing at the Botanical Garden in Rome were analysed. Correlation analysis of the data sets collected in the year 2006 confirmed the dependence among the considered leaf traits, in particular, RD was significantly (p<0.05) correlated with PN (r = 0.40). RD and PN increased from March to May [1.40±0.10 and 10.1±1.8 μmol(CO2) m –2 s –1 mean values of the period, respectively], when air temperature was in the range 14.8–25.2 °C, underlining the highest metabolic activity in the period of the maximum vegetative activity that favoured biomass accumulation. On the contrary, the highest RD [1.60±0.02 μmol(CO2) m –2 s –1 ], associated to the lowest PN rates (44 % of the maximum) and carbon use efficiency (CUE) in July underlined the mobilization of stored material during drought stress by a higher air temperature (32.7 °C).